Grief and Healing: the use of visual metaphors in Alfonso Cuarón Gravity 2013 - Nedjima Ouafa; Lamouri Oum elkhir (University of Eloued جامعة الوادي, 2025)
This study examines Alfonso Cuarón’s film Gravity (2013) as a profound cinematic exploration of grief and healing, suggesting that its visual devices serve more than an adornment or narrative luxuriation, but provide a necessity to represent psychologically the trauma and resolution Using a formalist analysis of foregrounded cinematic elements — cinematography, mise-en-scène, and iconic visuals (e.g., void/vacuum of space, debris reoccurrences, weightlessness/fetal positions, elemental rebirth) — the study visually traces the disjointed progression through various stages/models of grief (including Kubler-Ross’ 5-stages). The close reading demonstrates how Gravity utilizes its immersive audio-visual vocabulary to represent protagonist Dr. Ryan Stone’s process of moving from emotional paralysis and isolation to a sense of empowerment and revitalization, thus rendering subjective emotional states into universally archetypical narrative experience. This transdisciplinary study moves beyond dialogue to contest anti-trauma narratives, thereby offering a critical examination of how trauma is visually represented on screen. يقوم هذا البحث على دراسة فيلم " الجاذبية "(2023) للمخرج ألفونسو كوارون باعتباره استكشافًا سينمائيًا عميقًا للحزن والشفاء، اشارة إلى أن استعاراته البصرية تخدم أكثر من مجرد زينة أو ترف سردي، ولكنها توفر ضرورة لتمثيل الصدمة والحل نفسياً باستخدام تحليل شكلي للعناصر السينمائية المقدمة - التصوير السينمائي، والميزانسين، والمرئيات الأيقونية (على سبيل المثال، الفراغ / فراغ الفضاء، وتكرار الحطام، وانعدام الوزن / وضعية الجنين، والولادة الأولية) - تتبع الدراسة بصريًا التقدم غير المترابط من خلال مراحل / نماذج مختلفة من الحزن (بما في ذلك المراحل الخمس لكوبلر روس). توضح القراءة الدقيقة كيف يستخدم فيلم " الجاذبية " مفرداته السمعية والبصرية الغامرة لتمثيل عملية انتقال بطلة الرواية الدكتورة رايان ستون من الشلل العاطفي والعزلة إلى الشعور بالتمكن والنشاط، وبالتالي تحويل الحالات العاطفية الذاتية إلى تجربة سردية نموذجية عالميًا. إن هذا العلاج المتعدد التخصصات لنظريات السينما وعلم النفس حول الحزن لا يتفق مع "ثقافة الإغلاق" والسرد المضاد للصدمة، بما في ذلك التفسيرات النفسية في هذه المناقشة بما يتجاوز مجرد الحوار، وبالتالي تقديم مساهمة قيمة في إثارة إشكالية التمثيلات البصرية للصدمة الممثلة على الشاشة. الكلمات المفتاحية: السرد السينمائي، الحزن، الشفاء، الصدمة، الاستعارة البصرية.
Master's Degree In Literature and Civilization. 2025
Keywords: السرد السينمائي، الحزن، الشفاء، الصدمة، الاستعارة البصرية; Cinematic storytelling; grief; healing; trauma; visual metaphor